Absence of Severe Acute Respiratory Syndrome Coronavirus 2 Neutralizing Activity in Prepandemic Sera From Individuals With Recent Seasonal Coronavirus Infection - Poston, Daniel (Clin Infect Dis, 2020)
Cross-reactive immune responses elicited by seasonal coronaviruses might affect severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) susceptibility and disease outcomes. We measured neutralizing activity against SARS-CoV-2 in prepandemic sera from patients with prior polymerase chain reaction scan-confirmed seasonal coronavirus infection. Although neutralizing activity against seasonal coronaviruses was detected in nearly all sera, cross-reactive neutralizing activity against SARS-CoV-2 was undetectable.